2015
DOI: 10.1016/j.ebiom.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced CD8 T-lymphocyte Apoptosis as a Predictor of Breast Fibrosis After Radiotherapy: Results of the Prospective Multicenter French Trial

Abstract: BackgroundMonocentric cohorts suggested that radiation-induced CD8 T-lymphocyte apoptosis (RILA) can predict late toxicity after curative intent radiotherapy (RT). We assessed the role of RILA as a predictor of breast fibrosis (bf +) after adjuvant breast RT in a prospective multicenter trial.MethodsA total of 502 breast-cancer patients (pts) treated by conservative surgery and adjuvant RT were recruited at ten centers. RILA was assessed before RT by flow cytometry. Impact of RILA on bf + (primary endpoint) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 31 publications
(42 reference statements)
4
90
0
Order By: Relevance
“…It is widely accepted that in most cases no single gene is responsible for radiosensitivity; therefore, research is focused on gene expression and single polymorphism patterns, but both are highly expensive. On the other hand, “Radiation‐induced CD8 T‐lymphocyte Apoptosis” method has negative predictive value and marks patient population with no radiation toxicity risk . The method uses lymphocytes as normal tissue surrogate and has been tested in large clinical cohort and at various tumour sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that in most cases no single gene is responsible for radiosensitivity; therefore, research is focused on gene expression and single polymorphism patterns, but both are highly expensive. On the other hand, “Radiation‐induced CD8 T‐lymphocyte Apoptosis” method has negative predictive value and marks patient population with no radiation toxicity risk . The method uses lymphocytes as normal tissue surrogate and has been tested in large clinical cohort and at various tumour sites.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicentre study including 502 breast cancer patients, 86.4% showed late side effects 3 years after radiotherapy, of which 47.8% of patients were grade 1, 13.4% grade 2, and 0.6% grade 3+ fibrosis . Others published 6%, 12.6%, and even 23% of ≥grade 2 fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on methods first developed by Crompton et al . (127), prospective studies have demonstrated a correlation between a decrease in radiation-induced apoptosis after an 8 Gy exposure in vitro and an increase in RIF (128, 129). This method has the advantage of being simple, rapid, reproducible and minimally invasive.…”
Section: Predictive Biomarkers For Radiation Fibrosismentioning
confidence: 99%
“…Using this approach, it has been reported that the response of CD4 and CD8 T-lymphocytes to irradiation correlates with radiation-induced late effects following radiotherapy (Mirjolet et al , 2016; Azria et al , 2015). Most notably, an inverse correlation has been reported between radiation-induced T-lymphocyte apoptosis, particularly for CD8 cells, with the development of late effects in patients from whom the lymphocytes were derived.…”
Section: Radiogenomics Overviewmentioning
confidence: 99%